1998
DOI: 10.1037/0022-006x.66.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Empirically supported treatments: Implications for training.

Abstract: This article discusses the role of empirically supported treatments (ESTs) in the training of clinical psychologists. Training in ESTs can be integrated in ways that vary depending on the level of training and setting. Predoctoral programs, internships, postdoctoral programs, and continuing education are discussed in regard to special challenges and sequencing of training. A preliminary set of guidelines for training in ESTS is suggested. A positive impetus for training in EST skills is the current Guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 36 publications
2
119
0
1
Order By: Relevance
“…We agree with Calhoun et al (1998) that what is often absent in many manuals are therapeutic guidelines for what to do when confronted with in-session dilemmas. Work is currently underway to develop more clinically flexible manuals, including guidelines for what to do when one encounters problematic clinical situations (P. C. Kendall, personal communication, April 17, 1997).…”
Section: Designing Better Therapy Manualssupporting
confidence: 60%
See 2 more Smart Citations
“…We agree with Calhoun et al (1998) that what is often absent in many manuals are therapeutic guidelines for what to do when confronted with in-session dilemmas. Work is currently underway to develop more clinically flexible manuals, including guidelines for what to do when one encounters problematic clinical situations (P. C. Kendall, personal communication, April 17, 1997).…”
Section: Designing Better Therapy Manualssupporting
confidence: 60%
“…Thus, we randomly assign Diagnostic and Statistical Manual of Mental Disorders ( DSM ) diagnosed patients to treatments and predetermine how many sessions will be needed to bring about clinically meaningful change. Of necessity, this all contributes to the gap between research and the way therapy is practiced in the real world, a point acknowledged by Calhoun, Moras, Pilkonis, and Rehm (1998) , DeRubeis and Crits-Christoph (1998) , and Kazdin and Weisz (1998) . Should insurance companies begin to use information on empirically validated or supported therapies to certify the type-and length-of interventions they deem reasonable, the research-practice gap may be closed for us by others.…”
Section: From Time To Time Psychotherapy Researchers Have Complainedmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of implications are considered, and again a diversity of viewpoints was sought. The commentaries do not endorse a single-minded perspective but instead consider both the favorable and unfavorable issues facing the empirical evaluation and training of psychological therapy (e.g., Calhoun, Moras, Pilkonis, & Rehm, 1998 ;Davison, 1998 ).…”
Section: Comments On the Special Sectionmentioning
confidence: 99%
“…Addis (1997) and Calhoun, Moras, Pilkonis, and Rehm (1998), for example, suggested that much more attention needs to be paid to encouraging the flexible use of plans and strategies provided in treatment manuals. Many manuals inadvertently promote rule-governed behavior that may not be appropriate in all instances (i.e., when the client does X, the therapist should do Y).…”
Section: Rcts and Treatment Manualsmentioning
confidence: 99%